Clinical assessment of a novel recombinant simian adenovirus ChAdOx1 as a vectored vaccine expressing conserved Influenza A antigens. - Antrobus, R; Coughlan, L; Berthoud, T; Dicks, MD; Hill, A; Lambe, T; Gilbert, S (2014)
Adenoviruses are potent vectors for inducing and boosting cellular immunity to encoded recombinant antigens. However, the widespread seroprevalence of neutralizing antibodies to common human adenovirus serotypes limits their use. Simian adenoviruses do not suffer from the same drawbacks. We have constructed a replication-deficient chimpanzee adenovirus-vectored vaccine expressing the conserved influenza antigens, nucleoprotein (NP), and matrix protein 1 (M1). Here, we report safety and T-cell immunogenicity following vaccination with this novel recombinant simian adenovirus, ChAdOx1 NP+M1, in a first in human dose-escalation study using a 3+3 study design, followed by boosting with modified vaccinia virus Ankara expressing the same antigens in some volunteers. We demonstrate ChAdOx1 NP+M1 to be safe and immunogenic. ChAdOx1 is a promising vaccine vector that could be used to deliver vaccine antigens where strong cellular immune responses are required for protection.